The Influence of Effective Communication and Responsiveness of Pediatricians on Patient Loyalty with Patient Trust as an Intervening Variable at the Depok Hospital Executive Polyclinic - Sri Djuniarti; Kemala Rita; Idrus Jus'at (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
Patient loyalty is an important thing that a hospital needs to have because it describes the performance of a hospital. This research aims to determine the effect of effective communication and doctor responsiveness on patient loyalty and patient trust as an interventionist in the Polyclinic at one of the hospitals in Depok. The research population was all parents of pediatric patients visiting the executive polyclinic at Depok Hospital who had previously visited the executive polyclinic. The sample consisted of 111 respondents. The sample size was measured using G*Power software (Error 0.05; Effect size 0.3; power 0.95; sample size 111). The data analysis method uses path analysis. The research results show that effective doctor communication has a positive effect on patient loyalty. Doctor responsiveness has a positive effect on patient loyalty. Effective communication from doctors has a positive effect on patient trust. Doctors' responsiveness has a positive effect on patient confidence. Patient trust has no effect on patient loyalty. Trust does not mediate the effect of effective communication and doctor responsiveness on patient loyalty. This research contributes to efforts to increase patient loyalty through factors such as effective doctor communication, doctor responsiveness, and patient trust in the health sector in Indonesia.